Produtividade, qualidade fisiológica e composição química de sementes de crambe em diferentes doses de fósforo - Vazquez, Gisele Herbst [UNESP] (2014)
The crambe is a brassica with high content of oil used for biodiesel production and that has aroused interest in the short cycle and low production cost. However, there are doubts about their response to phosphated fertilization. The objective of this study was to evaluate the effect of different doses of phosphorus on yield, physiological quality, chemical composition and oil content of crambe seeds. The treatments consisted of five doses of phosphorus (0, 25, 50, 75 and 100 kg ha(-1)) applied at sowing. There was no effect of phosphorus on mineral composition and oil content of the seeds of crambe that showed the following averages: 30.11 N, 7.46 P, 7.35 K, Ca 10.06, 6.58 mg and 8.98 g kg(-1) S; 36.25 Cu, Fe 169.40, 36.75 Mn 73.60 mg kg(-1) Zn and 30.22% oil. It was concluded that the productivity of crambe increases with phosphorus rates of up to 100 kg ha(-1), but its use does not affect the survival rate of plants, dry mass, the mass of thousand seeds, the physiological quality, chemical composition and oil content of the seed.